Early hominins in Europe: The Galerian migration hypothesis. (15th January 2018) - Muttoni, Giovanni; Scardia, Giancarlo; Kent, Dennis V.
Abstract: Our updated review of sites bearing hominin remains and/or tools from Europe, including new findings from the Balkans, still indicates that the only compelling evidence of main hominin presence in these regions was only since ∼0.9 million years ago (Ma), bracketed by the end of the Jaramillo geomagnetic polarity subchron (0.99 Ma) and the Brunhes-Matuyama polarity chron boundary (0.78 Ma). This time window straddled the late Early Pleistocene climate transition (EPT) at the onset of enhanced glacial/interglacial activity that reverberated worldwide. Europe may have become initially populated during the EPT when, possibly for the first time in the Pleistocene, vast and exploitable ecosystems were generated along the eustatically emergent Po-Danube terrestrial conduit. These newly formed settings, characterized by stable terrestrial lowlands with open grasslands and reduced woody cover especially during glacial/interglacial transitions, are regarded as optimal ecosystems for several large Galerian immigrant mammals such as African and Asian megaherbivores, possibly linked with hominins in a common food web, to expand into en route to Europe. The question of when hominins first arrived in Europe thus places the issue in the context of changes in climate, paleogeography and faunal associations as potential environmental drivers and controlling agents in a specific time frame, a key feature of the Galerian migration hypothesis. Highlights: The Galerian hypothesis is a testable model for the timing of the earliest main peopling of Europe. The hypothesis posits a close linkage between oldest hominin sites and the climatic turnover of the late Early Pleistocene. Hominins entered Europe at 0.9 Ma with mammals from Africa and Asia across a newly opened Po-Danube migration conduit.